Dynamic Histone H3 Modifications Regulate Meiosis Initiation via Respiration - Shi, Jian; Ma, Yanjie; Hua, Hui; Liu, Yujiao; Li, Wei; Yu, Hongxiu; Liu, Chao (Frontiers in Cell and Developmental Biology, 2021)
Meiosis is essential for genetic stability and diversity during sexual reproduction in most eukaryotes. Chromatin structure and gene expression are drastically changed during meiosis, and various histone modifications have been reported to participate in this unique process. However, the dynamic of histone modifications during meiosis is still not well investigated. Here, by using multiple reaction monitoring (MRM) based LC-MS/MS, we detected dynamic changes of histone H3 lysine post-translational modifications (PTMs). We firstly quantified the precise percentage of H3 modifications on different lysine sites during mouse and yeast meiosis, and found H3 acetylation and methylation were dramatically changed. To further study the potential functions of H3 acetylation and methylation in meiosis, we performed histone H3 lysine mutant screening in yeast, and found that yeast strains lacking H3K18 acetylation (H3K18ac) failed to initiate meiosis due to insufficient IME1 expression. Further studies showed that the absence of H3K18ac impaired respiration, leading to the reduction of Rim101p, which further upregulated a negative regulator of IME1 transcription, Smp1p. Together, our studies reveal a novel meiosis initiation pathway mediated by histone H3 modifications.